Smart Trashcan Using IOT System - MOHAMAD FUAD, MOHAMAD FARIZ IMAN; MOHAMAD HEZRI , (Progress in Engineering Application and Technology, 2023)
The development of Internet of Things (IoT) nowadays is essential to better electronics and electrical appliances usage. The Smart Trash Can using IoT System is a way to improve the management of our daily waste in everyday life. Having a trashcan in houses is practically an essential to every person. The management of trash by people differs individually as they have their own ways to throw out the trash. A pile of trash in the trash can will causes a bad odour to house and even workspace. A trashcan that is not manage properly will cause the trash can to be full and overflowing. This will affect the cleanliness and the view of house or the workplace. To manage the situation and properly have a efficient management of trash disposing system in a workplace our home, the Smart Trash Can using IoT System is introduced. This project will develop a system that can detect the level inside of the trash that can alert users. The ultrasonic sensor in the Trash Can will detect the distance of the trash inside the    trashcan when the trash reaches the threshold value. The NodeMCU which is the ESP8266 controls the system which can link to any cloud platform and in this project, it is connected to the Telegram Messenger application. Users will be able to receive notifications on their smartphones or computers as Telegram can be accessed in all platforms.  In conclusion the uses of Smart Trash Can using IoT system helps reducing time to manage trash disposing in a hectic schedule faced by everyone